A Rare Case of Pigmented Eccrine Poroma on the Trunk Mimicking Malignant Melanoma - Saman Al‐Zahawi; Alireza Ghanadan; HamidReza Mahmoudi; Zahra Razavi (Clinical Case Reports)
ABSTRACT Representative clinical images in this study can increase awareness regarding the clinical similarity between this benign adnexal tumor and malignant melanoma and highlight the importance of pathological examination.